Electronic Archives Management to Realizing the Development of Information and Communication Technology in Achieve SDGs in Kendal Village, Sekaran District, Lamongan Regency - Karimah, Arzetya Fitri Al; Gading Gamaputra; Agus Prasetyawan; Prasetyo Isbandono; Weni Rosdiana; Yuni Lestari; Noviyanti; Dian Arlupi Utami; Isnaini Fitri Effendi; Naufal Hanif Ramadhan (Universitas Muhammadiyah Sidoarjo, 2022)
Archiving activities are part of the dministrative activities in an organization, which are very important. Archival management is a major factor in supporting the course of administrative activities in an organization. However, in practice, there are still organizations that are lacking in managing archives, so it can also affect the service process to the community. The purpose of this study was to determine the application of electronic mail archiving applications in the form of APEL SISA in Kendel Village to realize the development of information and communication technology in achieving the Village SDGs. The method used is descriptive qualitative. The focus of this research refers to the theory of Muhidin and Winata (2016) that digital archive management activities include two things, namely archive storage and archive retrieval. The data collection techniques in this study were through interviews and observation. The results of this study indicate that by using APEL SISA, archive storage in Kendal Village, which was originally manual, becomes more effective and efficient in providing services to the community, and electronic retrieval of archives can facilitate archive management at the Kendal Village office. Based on this, the management of archives in Kendal Village needs to be done all electronically to make it easier to manage archives that are stored and find back archives when needed.